Depression in public officials during the COVID-19 pandemic in Paraguay: a web-based study - Ji Eon Kim; Ji Ho Lee; Yanghee Kang; Sun Ha Lee; Hyein Shin; Nadia Rönnebeck; Renato Rönnebeck; Eun Woo Nam (BMC, 2021)
Abstract Background According to the World Health Organization, the coronavirus disease 2019 (COVID-19) pandemic has created situations that have a negative effect on people and threaten their mental health. Paraguay announced the Estado de Emergencia Sanitaria (Presidential Decree No. 3456) on March 16, 2020, which was followed by the imposition of a 24-h restriction on movement order on March 21. Self-quarantine at home may have been the most effective method of preventing the spread of infectious diseases; however, with the global pandemic becoming more prolonged and the consequent lengthening of the 24-h self-quarantine period, it is highly probable that both physical and psychological problems will arise. Methods In this study, a web-based cross-sectional method was used to analyze the factors influencing COVID-19-induced depressive feelings in Paraguayan public officials. Results Public officials reported a high level of depressive symptoms with a high level of apprehension in early stage of COVID-19. In addition, this study identified that when the self-quarantine period increased, levels of depressive feelings also increased. Since self-quarantine is characterized by the requirement that individuals endure an undetermined period within a confined area, it may have caused stress and anxiety, as well as the consequent experience of depressive feelings. Conclusions Paraguayan government should develop a program for the delivery of mental health care and services to public officials in COVID-19 Pandemic period. Moreover, a program is required for people facing deteriorating mental health due to social isolation and loneliness caused by social distancing during the prolonged period of self-quarantine. Finally, mental health care programs should be organized in a community-focused way by utilizing online systems to enhance the effectiveness of mental health recovery.